Middle Powers and the Global South: Strategic Autonomy in Contemporary Global Politics - Iqbal Reza Satria (Pen of Global Politics, 2026)
Contemporary global politics is increasingly shaped by a more complex distribution of power in which middle powers and actors from the Global South play more visible roles in diplomacy, governance, and order negotiation. At the same time, intensifying geopolitical rivalry and institutional fragmentation have made strategic autonomy a central concern for states seeking flexibility without full alignment. Strategic autonomy is examined here as a key framework for understanding how middle powers and the Global South navigate hierarchy, dependence, and competing centers of power. The article uses a qualitative research design based on document analysis and is guided by an analytical framework that combines middle-power theory, Global South perspectives, and an order-based understanding of agency and constraint. Data are drawn from official foreign policy statements, diplomatic speeches, summit declarations, international organization records, policy reports, and scholarly works relevant to strategic autonomy and contemporary global order. The analysis focuses on diversified partnerships, structural dependency, institutional engagement, alignment flexibility, and the relationship between autonomy and fragmented international politics. Strategic autonomy emerges as a relational and flexible strategy through which states seek to preserve room for maneuver while operating within unequal global structures. Contemporary autonomy is best understood not as absolute independence, but as a negotiated practice of managing interdependence, hierarchy, and geopolitical pressure. The article contributes to the field by bringing middle-power analysis and Global South perspectives into a more coherent conceptual dialogue on agency, order negotiation, and strategic flexibility in world politics.